2007
DOI: 10.1016/j.ygcen.2007.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide and the mammalian circadian system

Abstract: In mammals, the circadian oscillators that drive daily behavioral and endocrine rhythms are located in the hypothalamic suprachiasmatic nucleus (SCN). While the SCN is anatomically well-situated to receive and transmit temporal cues to the rest of the brain and periphery, there are many holes in our understanding of how this temporal regulation occurs. Unanswered questions include how cell autonomous circadian oscillations within the SCN remain synchronized to each other as well as communicate temporal informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
143
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 99 publications
(130 reference statements)
3
143
0
Order By: Relevance
“…The conclusion here that VIP-VPAC2R signaling dominates is consistent with the observation that loss of VIP or VPAC2R abolishes circadian rhythms in most behaviors and physiological processes in most mice (11,12). That GRP and AVP can, in the absence of VIP, suffice to sustain daily cycling is consistent with the observation that some or all VIP/VPAC2R-deficient mice can still show synchronized circadian rhythms under some conditions (16) and that GRP can induce rhythms in VPAC2R-null SCN (17).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The conclusion here that VIP-VPAC2R signaling dominates is consistent with the observation that loss of VIP or VPAC2R abolishes circadian rhythms in most behaviors and physiological processes in most mice (11,12). That GRP and AVP can, in the absence of VIP, suffice to sustain daily cycling is consistent with the observation that some or all VIP/VPAC2R-deficient mice can still show synchronized circadian rhythms under some conditions (16) and that GRP can induce rhythms in VPAC2R-null SCN (17).…”
supporting
confidence: 88%
“…They started by asking whether the SCN taken from a wild-type mouse is capable of rescuing daily rhythms in the SCN taken from an arrhythmic mouse. Previous studies had demonstrated that loss of vasoactive intestinal polypeptide (VIP) or its cognate receptor, VPAC2R (encoded by the Vipr2 gene) abolished synchronized circadian rhythms in the SCN and in locomotor behavior (11,12). The new study (2) shows that wild-type SCN can quickly restore rhythms to SCN lacking VIP.…”
mentioning
confidence: 98%
“…There is also evidence which suggests that VIP may play a role in the regulation of the HPA-axis (Nussdorfer et al, 1998). VIP may also play a role centrally where it is a major peptide involved in the suprachiasmatic nucleus of the hypothalamus, which is the circadian pacemaker (Vosko et al, 2007). However, it is important to note that VIP's role in the CNS may have no correlation with its role in the parasympathetic nerves.…”
Section: Salivary Vasoactive Intestinal Peptide As a Marker For Stressmentioning
confidence: 99%
“…Other studies highlight the importance of VIP in relation to the regulation of circadian variations. Evidence suggests that VIP is important for the normal functioning of the suprachiasmatic nucleus in the hypothalamus (Loh et al, 2008;Vosko et al, 2007;Piggins et al, 2003). A study performed in VIP knockout mice demonstrates that the circadian rhythms of ACTH and corticosterone are lost and the authors suggest a role for VIP in regulating the mammalian master clock (Loh et al, 2008).…”
Section: Circadian Rhythms and Cortisol Dhea Amylase And Vipmentioning
confidence: 99%
See 1 more Smart Citation